LAB Fit - TREATMENT OF EXPERIMENTAL DATA

BY WILTON E CLEIDE PEREIRA DA SILVA

DF/CCT/UFPB - CAMPINA GRANDE, PB BRAZIL

R. Artur Monteiro Viana, 55 Campina Grande

Paraíba Brasil phone 021 83 3332962

THEORY: TRATAMENTO DE DADOS EXPERIMENTAIS - WILTON AND CLEIDE

UFPB/EDITORA UNIVERSITÁRIA CX POSTAL 5081 J. PESSOA, PB

58010-970 BRAZIL - PHONE 021 83 216 7147

# FUNCTIONS OF THE LIBRARY

FUNCTIONS OF THE LIBRARY (WITH 1 INDEPENDENT VARIABLE)

N.   1: Y = A <--- Constant

N.   2: Y = A*X <--- Straight line (origin)

N.   3: Y = A*X**2 <--- Parabola (vert at the origin)

N.   4: Y = A/X <--- Hyperbola

N.   5: Y = A/X**2 <--- 2nd order Hyperbola

N.   6: Y = A*X+B <--- Straight line

N.   7: Y = A*X**2+B <--- Parabola

N.   8: Y = A/X+B <--- Hiperbola

N.   9: Y = A/X**2+B <--- 2nd order Hyperbola

N  10: Y = A*X**B <--- Power

N.  11: Y = A*EXP(B*X) <--- Exponential

N.  12: Y = A*(Ln(X))**B <--- Pow log

N.  13: Y = A*EXP(B/X) <--- Modified Exponential

N.  14: Y = A*X**3 <--- Parabola (vertex at the origin)

N.  15: Y = A*X**4 <--- Parabola (vertex at the origin)

N.  16: Y = 1/(A*X+B) <--- Inverse of straight line

N.  17: Y = X/(A+B*X) <--- Inverse of hyperbola

N.  18: Y = A*B**X <--- Modified power

N.  19: Y = A*B**(1/X) <--- Root (mod exponential)

N.  20: Y = A*X**(B*X) <--- Super geometric

N.  21: Y = A*X**(B/X) <--- Modified geometric

N.  22: Y = A+B*LnX <--- Logarithmic

N.  23: Y = 1/(A+B*LnX) <--- Inverse of logarithmic

N.  24: Y = A*X+B*X**2 <--- Parabola (origin)

N.  25: Y = SQRT(A-(X-B)**2) <--- Arc of circle

N.  26: Y = X/(A+B*X**2) <--- Straight / parabola

N.  27: Y = A*(B**X)*X**C <--- Hoerl

N.  28: Y = A*(B**(1/X))*X**C <--- Mod Hoerl

N.  29: Y = A*EXP(((X-B)**2)/C) <--- Gaussian

N.  30: Y = A*EXP(((LnX-B)**2)/C) <--- Log Gaussian

N.  31: Y = 1/(A*(X+B)**2)+C) <--- Cauchy

N.  32: Y = A*(X**B)*(1-X)**C <--- Beta

N.  33: Y = A+B/X+C/X**2 <--- 2nd order Hyperbola

N.  34: Y = A*X+B*X**2+C*X**3 <--- 3nd order polynomial

N.  35: Y = A+B*X+C/X <--- Straight line and inverse

N.  36: Y = A+B*X+C*X**2 <--- Parabola

N.  37: Y = A*((X/B)**C)*EXP(X/B) <--- Gamma

N.  38: Y = 1/(A+B*X+C/X) <--- Inv: straight line and hiperbola

N.  39: Y = SQRT(A-B*(X-C)**2) <--- Ellipse

N.  40: Y = A+B*X+C/X**2 <--- Straight line + hyperbola

N.  41: Y = A+B*X**2+C/X <--- Parabola + hiperbola

N.  42: Y = A*X**(B+C*X) <--- Pow (2)

N.  43: Y = A*X**(B+C/X) <--- Pow (3)

N.  44: Y = A*X**(B+C*LnX) <--- Pow (4)

N.  45: Y = A*X**(B*X+C*X**2) <--- Pow (5)

N.  46: Y = A*EXP(B*X+C*X**0.5) <--- Exp (2)

N.  47: Y = A*EXP(B/X+C*X) <--- Exp (3)

N.  48: Y = (A+X)/(B+C*X) <--- Straight line / straight

N.  49: Y = (A+X)/(B+C*X**2) <--- Straight line / parabola

N.  50: Y = A+B*X+C*X**2+D*X**3

N.  51: Y = A+B*X+C*X**2+D*X**3+E*X**4

N.  52: Y = A+B*X+C*X**2+D*X**3+E*X**4+F*X**5

N.  53: Y = A+B*X+C*X**2+D*X**3+E*X**4+F*X**5+G*X**6

N.  54: Y = A*EXP(B*X)+C*EXP(D*X) <--- 2 exponentials

N.  55: Y = A*(EXP(B*X)-EXP(C*X)) <--- Assoc exp

N.  56: Y = A*X**B+C*X**D <--- 2 pow

N.  57: Y = A+B*EXP(C*X) <--- 1 exp + c

N.  58: Y = A*(1-EXP(B*X)) <--- Assoc exp

N.  59: Y = A*COS(B*X) <--- Cossine

N.  60: Y = A*COS(B*X+C) <--- Cossine

N.  61: Y = A*SEN(B*X) <--- Sine

N.  62: Y = A*SEN(B*X+C) <--- Sine

N.  63: Y = A*TAN(B*X) <--- Tangent

N.  64: Y = A*TAN(B*X+C) <--- Tangent

N.  65: Y = A*ACOS(B*X)+C <--- Inv cossine

N.  66: Y = A*ATAN(B*X)+C <--- Inv tangent

N.  67: Y = A*ASEN(B*X)+C <--- Inv sine

N.  68: Y = A*TAN(B*X+C)+D <--- Tangent

N.  69: Y = A*SEN(B*X+C)+D <--- Sine

N.  70: Y = A*COS(B*X+C)+D <--- Cossine

N.  71: Y = A*COS(D*X)+B*COS(2*D*X)+C*COS(3*D*X)

N.  72: Y = A*COS(1*E*X+D)+...+C*COS(3*E*X+D)

N.  73: Y = A*COS(1*E*X+D)+...+C*COS(3*E*X+D)+F

N.  74: Y = A*X**B+C <--- 1 pow + c

N.  75: Y = A*X**B+C*X**D+E <--- 2 pow + c

N.  77: Y = A*X**B+C*EXP(D*X) <--- Pow + exp

N.  78: Y = A*X**B+C*EXP(D*X)+E <--- Pow + exp + c

N.  79: Y = (A*X**B)*(C-X)**D <--- Mod Beta

N.  80: Y = A*EXP(B*EXP(C*X)) <--- Gompertz

N.  81: Y = A/(1+B*EXP(C*X)) <--- Logistic

N.  82: Y = A/(B+X**C) <--- Langmuir

N.  83: Y = A/(1+B*X**C)**2 <-- Mod Langmuir

N.  84: Y = (A+B*X**C)/(D+X**C) <--- MMF

N.  85: Y = (A+B*X)**C <--- Bleasdale (Shifted power)

N.  86: Y = (A+B*SQRT(X))**C <--- Mod Bleasdale

N.  87: Y = 1/(A+B*X**C) <--- Harris

N.  88: Y = 1/(A+B*EXP(C*X))**D <--- Richards

N.  89: Y = A*EXP(B/X)+C <--- Mod exp + c

N.  90: Y = 1/(A*X+B)+C <--- Inv straight line + c

N.  91: Y = X/(A+B*X)+C <--- Inv hyperbola + c

N.  92: Y = (A*X**B)*(C-X)**D+E <--- Mod Beta + c

N.  93: Y = A*EXP(B*EXP(C*X))+D <--- Gompertz + c

N.  94: Y = A/(1+B*EXP(C*X))+D <--- Logistic + c

N.  95: Y = EXP(A+B/X+C*Ln(X)) <--- Vapor Pressure (mod Hoerl)

N.  96: Y = A/(1+B*X**C)**2+D <--- Mod Langmuir + c

N.  97: Y = (A+B*X**C)/(D+X**C)+E <--- MMF + c

N.  98: Y = (A+B*X)**C+D <--- Bleasdale (Shifted power) + c

N.  99: Y = (A+B*SQRT(X))**C+D <--- Mod Bleasdale +c

N. 100: Y = 1/(A+B*X**C)+D <--- Harris + c

N. 101: Y = 1/(A+B*EXP(C*X))**D+E <--- Richards + c

N. 102: Y = A*EXP(B*X**C) <--- Exp of pow

N. 103: Y = A*EXP(B*X**C)+D <--- Weibull

N. 104: Y = (A+B*X)/(1+C*X+D*X**2) <--- Rational

N. 105: Y = A*X**(B*X**C) <--- Freundich

N. 106: Y = X/(A+B*X+C*SQRT(X)) <--- Gunary

N. 107: Y = 1/(A+B*X**2)**C <--- Inv pow

N. 108: Y = A*(Ln(X))**B+C <--- Pow of log + c

N. 109: Y = A*Ln(X+B) <--- Mod Log

N. 110: Y = A*Ln(X+B)+C <--- Mod Log + c

N. 111: Y = A*X**B+C*EXP(D/X) <--- Pow + mod exp

N. 112: Y = A/X+B*X**C <--- Hyp + pow

N. 113: Y = A/X+B*EXP(C/X) <--- Hyp + mod exp

N. 114: Y = A/X+B*EXP(C*X) <--- Hyp. + exp

N. 115: Y = A*X*EXP(B*X) <-- Exp x straight line

N. 116: Y = A*EXP(B*X)/X <-- Hyp x exp

N. 117: Y = A*EXP(B/X)/X <-- Hyp. x mod exp

N. 118: Y = A*X**(B*X**C)+D <-- Freundich + c

N. 119: Y = X/(A+B*X+C*SQRT(X))+D <-- Gunary + c

N. 120: Y = 1/(A+B*X**2)**C+D <-- Inv pow + c

N. 121: Y = A*(X**B)*Ln(X) <-- Pow x log

N. 122: Y = A*(X**B)/Ln(X) <-- Pow / log

N. 123: Y = A*(X**B)*Ln(X+C) <-- Pow x log (2)

N. 124: Y = A*X**B+C*EXP(D/X)+E <-- Pow + mod exp +c

N. 125: Y = A/X+B*X**C+D <-- Hyp + pow + c

N. 126: Y = A/X+B*EXP(C/X)+D <-- Hyp + mod exp + c

N. 127: Y = A/X+B*EXP(C*X)+D <-- Hyp + exp + c

N. 128: Y = A*B**X+C <--- Mod pow+ c

N. 129: Y = A*B**(1/X)+C <--- Root + c

N. 130: Y = A*X**(B*X)+C <--- Super geometric + c

N. 131: Y = A*X**(B/X)+C <--- Mod geometric + c

N. 132: Y = 1/(A+B*LnX)+C <--- Inv log + c

N. 133: Y = A*(Ln(X+B))**C <--- Pow of mod log

N. 134: Y = A*(Ln(X+B))**C+D <--- Pow of mod log + c

N. 135: Y = A*(B**X)*X**C+D <--- Hoerl + c

N. 136: Y = A*(B**(1/X))*X**C+D <--- Mod Hoerl + c

N. 137: Y = A*EXP(((LnX-B)**2)/C)+D <--- Log Gaussian + c

N. 138: Y = 1/(A*(X+B)**2+C)+D <--- Cauchy + c

N. 139: Y = A*((X/B)**C)*EXP(X/B)+D <--- Gamma + c

N. 140: Y = A*EXP(((X-B)**2)/C)+D <--- Gaussian + c

N. 141: Y = 1/(A+B*X+C/X)+D

N. 142: Y = A*X**(B+C*X)+D <--- Pow (2) + c

N. 143: Y = A*X**(B+C/X)+D <--- Pow (3) + c

N. 144: Y = A*X**(B+C*LnX)+D <--- Pow (4) + c

N. 145: Y = A*X**(B*X+C*X**2)+D <--- Pow (5) + c

N. 146: Y = A*EXP(B*X+C*X**0.5)+D <--- Exp (2) + c

N. 147: Y = A*EXP(B/X+C*X)+D <--- Exp (3) + c

N. 148: Y = (A+X)/(B+C*X)+D*X <--- Straight / straight + straight

N. 149: Y = (A+X)/(B+C*X**2)+D <--- Straight line / parabola + c

N. 150: Y = A*SENH(B*X) <--- Hyperbolical sine

N. 151: Y = A*COSH(B*X) <--- Hiperbolical cosine

N. 152: Y = SQRT(A-(X-B)**2)+C <--- circle + c

N. 153: Y = SQRT(A-B*(X-C)**2)+D <--- Ellipse + c

N. 154:   Y = A*COSH(B*X) + C <--- Hiperbolical cossine + c

N. 155:   Y = A*SINH(B*X) + C <--- Hyperbolical sine + c

N. 156:   Y = SQRT(A-B*(X-C)**2)+D*X <--- Ellipse + Str

N. 157:   Y = A*X**(B/X)+C*X <--- Mod geometric + Str

N. 158:   Y = 1/(A+B*LnX)+C*X <--- Inv log + Str

N. 159:   Y = A*(Ln(X+B))**C+D*X

N. 160:   Y = A*(Ln(X+B))**C+D*X**2

N. 161:   Y = A*(B**X)*X**C+D*X <--- Hoerl + Str

N. 162:   Y = A*(B**(1/X))*X**C+D*X

N. 163:   Y = A*EXP(((LnX-B)**2)/C)+D*X

N. 164:   Y = 1/(A*(X+B)**2+C)+D*X <--- Cauchy + Str

N. 165:   Y = A*((X/B)**C)*EXP(X/B)+D*X

N. 166:   Y = A*EXP(((X-B)**2)/C)+D*X

N. 167:   Y = 1/(A+B*X+C/X)+D*X

N. 168:   Y = A*X**(B+C*X)+D*X <--- Pow (2) + Str

N. 169:   Y = A*X**(B+C/X)+D*X <--- Pow (3) + Str

N. 170:   Y = A*X**(B+C*LnX)+D*X <--- Pow (4) + Str

N. 171:   Y = A*X**(B*X+C*X**2)+D*X <--- Pow (5) + Str

N. 172:   Y = A*EXP(B*X+C*X**0.5)+D*X <--- Exp (2) + Str

N. 173:   Y = A*EXP(B/X+C*X)+D*X <--- Exp (3) + Str

N. 174:   Y = (A+X)/(B+C*X)+D*X**2 <--- Straight / straight + Parab

N. 175:   Y = (A+X)/(B+C*X**2)+D*X

N. 176:   Y = A*SINH(B*X)+C*X <--- Hyperbolical sine + Str

N. 177:   Y = A*COSH(B*X)+C*X <--- Hiperbolical cossine + Str

N. 178:   Y = SQRT(A-(X-B)**2)+C*X <--- circle + Str

N. 179:   Y = SQRT(A-B*(X-C)**2)+D*X**3 <--- Ellipse + Parab

N. 180:   Y = A*COSH(B*X)+C*X**2

N. 181:   Y = A*SINH(B*X)+C*X**2

N. 182:   Y = SQRT(A-B*(X-C)**2)+D*X**2

N. 183:   Y = A*X**(B/X)+C*Ln(X)

N. 184:   Y = 1/(A+B*LnX)+C*Ln(X)

N. 185:   Y = A*(Ln(X+B))**C+D*Ln(X)

N. 186:   Y = A*(Ln(X+B))**C+D*Ln(X)**2

N. 187:   Y = A*(B**X)*X**C+D*Ln(X)

N. 188:   Y = A*(B**(1/X))*X**C+D*Ln(X)

N. 189:   Y = A*EXP(((LnX-B)**2)/C)+D*Ln(X)

N. 190:   Y = 1/(A*(X+B)**2+C)+D*Ln(X)

N. 191:   Y = A*((X/B)**C)*EXP(X/B)+D*Ln(X)

N. 192:   Y = A*EXP(((X-B)**2)/C)+D*Ln(X)

N. 193:   Y = 1/(A+B*X+C/X)+D*Ln(X)

N. 194:   Y = A*X**(B+C*X)+D*Ln(X)

N. 195:   Y = A*X**(B+C/X)+D*Ln(X)

N. 196:   Y = A*X**(B+C*LnX)+D*Ln(X)

N. 197:   Y = A*X**(B*X+C*X**2)+D*Ln(X)

N. 198:   Y = A*EXP(B*X+C*X**0.5)+D*Ln(X)

N. 199:   Y = A*EXP(B/X+C*X)+D*Ln(X)

N. 200:   Y = (A+X)/(B+C*X)+D*Ln(X)**2

N. 201:   Y = (A+X)/(B+C*X**2)+D*Ln(X)

N. 202:   Y = A*SINH(B*X)+C*Ln(X)

N. 203:   Y = A*COSH(B*X)+C*Ln(X)

N. 204:   Y = SQRT(A-(X-B)**2)+C*Ln(X)

N. 205:   Y = SQRT(A-B*(X-C)**2)+D*Ln(X)

N. 206:   Y = A*COSH(B*X)+C*Ln(X)**2

N. 207:   Y = A*SINH(B*X)+C*Ln(X)**2

N. 208:   Y = SQRT(A-B*(X-C)**2)+D*Ln(X)**2

.                  .                  .

.                  .                  .

.                  .                  .

TECHNICAL RESERVATION FOR FUNCTIONS WITH 1 INDEPENDENT VARIABLE

.                  .                  .

.                  .                  .

.                  .                  .

FUNCTIONS OF THE LIBRARY (WITH 2 INDEPENDENT VARIABLES)

N. 300: Y=A*(X1**B)*X2**C <--- Pow x pow

N. 301: Y=X1/(A+B*X2) <--- Inv hyp (1)

N. 302: Y=X2/(A+B*X1) <--- Inv hyp (2)

N. 303: Y=A*X1**(B*X2) <--- Super geometric (1)

N. 304: Y=A*X2**(B*X1) <--- Super geometric (2)

N. 305: Y=A*X1**(B/X2) <--- Mod geometric (1)

N. 306: Y=A*X2**(B/X1) <--- Mod geometric (2)

N. 307: Y=A*X1+B*X2**2 <--- 2nd order (1)

N. 308: Y=A*X2+B*X1**2 <--- 2nd order (2)

N. 309: Y=X1/(A+B*X2**2) <--- Straight line / parabola (1)

N. 310: Y=X2/(A+B*X1**2) <--- Straight line / parabola (2)

N. 311: Y=A*(B**X1)*X2**C <--- Hoerl (1)

N. 312: Y=A*(B**X2)*X1**C <--- Hoerl (2)

N. 313: Y=A*(X1*X2)**B <--- Pow (1)

N. 314: Y=A*(X1/X2)**B <--- Pow (2)

N. 315: Y=A*(X1/X2)**B+C <--- Pow + c (3)

N. 316: Y=A*(B**(1/X1))*X2**C <--- Mod Hoerl (1)

N. 317: Y=A*(B**(1/X2))*X1**C <--- Mod Hoerl (2)

N. 318: Y=A+B/X1+C/X2**2 <--- 2nd order Hyperbola (1)

N. 319: Y=A+B/X2+C/X1**2 <--- 2nd order Hyperbola (2)

N. 320: Y=A+B*X1+C/X2 <--- Straight line + hyp (1)

N. 321: Y=A+B*X2+C/X1 <--- Straight line + hyp (2)

N. 322: Y=A*((X1/B)**C)*EXP(X2/B) <--- Gamma (1)

N. 323: Y=A*((X2/B)**C)*EXP(X1/B) <--- Gamma (2)

N. 324: Y=A+B*X1+C*X2**2 <--- Parabola (1)

N. 325: Y=A+B*X2+C*X1**2 <--- Parabola (2)

N. 326: Y=A*(X1**B)*X2**C+D <--- Pow x pow + c

N. 327: Y=X1/(A+B*X2)+C <--- Inv hyp + c (1)

N. 328: Y=X2/(A+B*X1)+C <--- Inv Hyp + c (2)

N. 329: Y=A*X1**(B*X2)+C <--- Super geometric + c (1)

N. 330: Y=A*X2**(B*X1)+C <--- Super geometric + c (2)

N. 331: Y=A*X1**(B/X2)+C <--- Mod geometric + c (1)

N. 332: Y=A*X2**(B/X1)+C <--- Mod geometric + c (2)

N. 333: Y=A*(B**(1/X1))*X2**C+D <--- Mod Hoerl + c (1)

N. 334: Y=A*(B**(1/X2))*X1**C+D <--- Mod Hoerl + c (2)

N. 335: Y=X1/(A+B*X2**2)+C <--- Straight line / parabola + c (1)

N. 336: Y=X2/(A+B*X1**2)+C <--- Straight line / parabola + c (2)

N. 337: Y=A*(B**X1)*X2**C+D <--- Hoerl + c (1)

N. 338: Y=A*(B**X2)*X1**C+D <--- Hoerl + c (2)

N. 339: Y=A*((X1/B)**C)*EXP(X2/B)+D <--- Gamma + c (1)

N. 340: Y=A*((X2/B)**C)*EXP(X1/B)+D <--- Gamma + c (2)

N. 341: Y=1/(A+B*X1+C/X2) <--- Inv: Straight line + hyp (1)

N. 342: Y=1/(A+B*X2+C/X1) <--- Inv: Straight line + hyp (1)

N. 343: Y=A+B*X1+C/X2**2 <--- Straight line + hyp (1)

N. 344: Y=A+B*X2+C/X1**2 <--- Straight line + hyp (1)

N. 345: Y=A*X1**(B+C*X2) <--- Pow (3)

N. 346: Y=A*X2**(B+C*X1) <--- Pow (4)

N. 347: Y=A*X1**(B+C/X2) <--- Pow (5)

N. 348: Y=A*X2**(B+C/X1) <--- Pow (6)

N. 349: Y=A*X1**(B+C*LnX2) <--- Pow (7)

N. 350: Y=A*X2**(B+C*LnX1) <--- Pow (8)

N. 351: Y=A*X2**(B+C/LnX1) <--- Pow (9)

N. 352: Y=A*X1**(B+C/LnX2) <-- Pow (10)

N. 353: Y=A*EXP(B*X1+C*X2**2) <-- Exp (1)

N. 354: Y=A*EXP(B*X2+C*X1**2) <-- Exp (2)

N. 355: Y=A*EXP(B/X1+C*X2) <-- Exp (3)

N. 356: Y=A*EXP(B/X2+C*X1) <-- Exp (4)

N. 357: Y=(A+X1)/(B+C*X2) <-- Straight line / Straight line (1)

N. 358: Y=(A+X2)/(B+C*X1) <-- Straight line / straight line (2)

N. 359: Y=(A+X1)/(B+C*X2**2) <-- Straight line / parabola (1)

N. 360: Y=(A+X2)/(B+C*X1**2) <-- Straight line / parabola (2)

N. 361: Y=A*EXP(B*X1)+C*EXP(D*X2) <-- 2 exp

N. 362: Y=A*(EXP(B*X1)-EXP(C*X2)) <-- Assoc exp

N. 363: Y=A*X1**B+C*X2**D <-- 2 pow

N. 364: Y=A*X1**B+C*EXP(D*X2) <-- Pow + exp (1)

N. 365: Y=A*X2**B+C*EXP(D*X1) <-- Pow + exp (2)

N. 366: Y=A*(X1**B)*(C-X2)**D <-- Mod Beta (1)

N. 367: Y=A*(X2**B)*(C-X1)**D <-- Mod Beta (2)

N. 368: Y=(A+B*X1**D)/(C+X2**D) <-- MMF (1)

N. 369: Y=(A+B*X2**D)/(C+X1**D) <-- MMF (2)

N. 370: Y=(A+B*X1)/(1+C*X2+D*X2**2) <-- Rational (1)

N. 371: Y=(A+B*X2)/(1+C*X1+D*X1**2) <-- Rational (2)

N. 372: Y=A*X1**(B*X2**C) <-- Freundich (1)

N. 373: Y=A*X2**(B*X1**C) <-- Freundich (2)

N. 374: Y=X1/(A+B*X2+C*SQRT(X2)) <-- Gunary (1)

N. 375: Y=X2/(A+B*X1+C*SQRT(X1)) <-- Gunary (2)

N. 376: Y=A*X1**B+C*EXP(D/X2) <-- Pow + mod exp (1)

N. 377: Y=A*X2**B+C*EXP(D/X1) <-- Pow + mod exp (2)

N. 378:   Y=A*EXP(((X1-B)**2)/C+((X2-D)**2)/E) <-- Gaussian

N. 379:   Y=A*EXP(((LnX1-B)**2)/C+((LnX2-D)**2)/E)

N. 380:   Y=A*X2**2+B*X2+C*X1+D

N. 381:   Y=A*X1**2+B*X1+C*X2+D

N. 382:   Y=A*X1**3+B*X1**2+C*X1+D*X2

N. 383:   Y=A*X2**3+B*X2**2+C*X2+D*X1

N. 384:   Y=A*X2**3+B*X2**2+C*X2+D*X1+E

N. 385:   Y=A*X1**3+B*X1**2+C*X1+D*X2+E

N. 386:   Y=EXP(A+B/X1+C*Ln(X2)) <-- Vapor Pressure (1)

N. 387:   Y=EXP(A+B/X2+C*Ln(X1)) <-- Vapor Pressure (2)

N. 388:   Y=EXP(A+B/X1+C*Ln(X2))+D <-- Vapor Pressure (3)

N. 389:   Y=EXP(A+B/X2+C*Ln(X1))+D <-- Vapor Pressure (4)

N. 390:   Y=A*(X1**B)*Ln(X2+C) <-- Pow x log (1)

N. 391:   Y=A*(X2**B)*Ln(X1+C) <-- Pow x log (2)

N. 392:   Y=A*(X1**B)*Ln(X2+C)+D <-- Pow x log (3)

N. 393:   Y=A*(X2**B)*Ln(X1+C)+D <-- Pow x log (4)

N. 394:   Y=A/X1+B*EXP(C/X2)+D <-- Hyp + mod exp (1)

N. 395:   Y=A/X2+B*EXP(C/X1)+D <-- Hyp + mod exp (2)

N. 396:   Y=A/X1+B*EXP(C*X2)+D <-- Hyp + exp (1)

N. 397:   Y=A/X2+B*EXP(C*X1)+D <-- Hyp + exp (2)

N. 398:   Y=A*X1**(B+C*X2)+D <-- Pow (3) + c

N. 399:   Y=A*X2**(B+C*X1)+D <-- Pow (4) + c

N. 400:   Y=A*X1**(B+C/X2)+D <-- Pow (5) + c

N. 401:   Y=A*X2**(B+C/X1)+D <-- Pow (6) + c

N. 402:   Y=A*X1**(B+C*LnX2)+D <-- Pow (7) + c

N. 403:   Y=A*X2**(B+C*LnX1)+D <-- Pow (8) + c

N. 404:   Y=A*X2**(B+C/LnX1)+D <-- Pow (9) + c

N. 405:   Y=A*X1**(B+C/LnX2)+D <-- Pow (10) + c

N. 406:   Y=A*EXP(B*X1+C*X2**2)+D <-- Exp (1) + c

N. 407:   Y=A*EXP(B*X2+C*X1**2)+D <-- Exp (2) + c

N. 408:   Y=A*EXP(B/X1+C*X2)+D <-- Exp (3) + c

N. 409:   Y=A*EXP(B/X2+C*X1)+D <-- Exp (4) + c

N. 410:   Y=(A+X1)/(B+C*X2)+D <-- Str / Str (1) + c

N. 411:   Y=(A+X2)/(B+C*X1)+D <-- Str / Str (2) + c

N. 412:   Y=(A+X1)/(B+C*X2**2)+D <-- Str / Parab (1) + c

N. 413:   Y=(A+X2)/(B+C*X1**2)+D <-- Str / Parab (2) + c

N. 414:   Y=A*X1**(B*X2**C)+D <-- Freundich (1) + c

N. 415:   Y=A*X2**(B*X1**C)+D <-- Freundich (2) + c

N. 416:   Y=A*X1+B*X2+C <-- Str + Str

N. 417:   Y=A*X1+B*X1**2+C*X2+D*X2**2 <-- Parab + Parab

N. 418:   Y=A*(X1**B)*Ln(X2+C)+D*X1

N. 419:   Y=A*(X2**B)*Ln(X1+C)+D*X1

N. 420:   Y=A/X1+B*EXP(C/X2)+D*X1

N. 421:   Y=A/X2+B*EXP(C/X1)+D*X1

N. 422:   Y=A/X1+B*EXP(C*X2)+D*X1

N. 423:   Y=A/X2+B*EXP(C*X1)+D*X1

N. 424:   Y=A*X1**(B+C*X2)+D*X1

N. 425:   Y=A*X2**(B+C*X1)+D*X1

N. 426:   Y=A*X1**(B+C/X2)+D*X1

N. 427:   Y=A*X2**(B+C/X1)+D*X1

N. 428:   Y=A*X1**(B+C*LnX2)+D*X1

N. 429:   Y=A*X2**(B+C*LnX1)+D*X1

N. 430:   Y=A*X2**(B+C/LnX1)+D*X1

N. 431:   Y=A*X1**(B+C/LnX2)+D*X1

N. 432:   Y=A*EXP(B*X1+C*X2**2)+D*X1

N. 433:   Y=A*EXP(B*X2+C*X1**2)+D*X1

N. 434:   Y=A*EXP(B/X1+C*X2)+D*X1

N. 435:   Y=A*EXP(B/X2+C*X1)+D*X1

N. 436:   Y=(A+X1)/(B+C*X2)+D*X1

N. 437:   Y=(A+X2)/(B+C*X1)+D*X1

N. 438:   Y=(A+X1)/(B+C*X2**2)+D*X1

N. 439:   Y=(A+X2)/(B+C*X1**2)+D*X1

N. 440:   Y=A*X1**(B*X2**C)+D*X1

N. 441:   Y=A*X2**(B*X1**C)+D*X1

N. 442:   Y=A*X1+B*X2+C*X1**4

N. 443:   Y=A*X1+B*X1**3+C*X2+D*X2**3 <-- Parab + Parab

N. 444:   Y=A*(X1**B)*Ln(X2+C)+D*X2

N. 445:   Y=A*(X2**B)*Ln(X1+C)+D*X2

N. 446:   Y=A/X1+B*EXP(C/X2)+D*X2

N. 447:   Y=A/X2+B*EXP(C/X1)+D*X2

N. 448:   Y=A/X1+B*EXP(C*X2)+D*X2

N. 449:   Y=A/X2+B*EXP(C*X1)+D*X2

N. 450:   Y=A*X1**(B+C*X2)+D*X2

N. 451:   Y=A*X2**(B+C*X1)+D*X2

N. 452:   Y=A*X1**(B+C/X2)+D*X2

N. 453:   Y=A*X2**(B+C/X1)+D*X2

N. 454:   Y=A*X1**(B+C*LnX2)+D*X2

N. 455:   Y=A*X2**(B+C*LnX1)+D*X2

N. 456:   Y=A*X2**(B+C/LnX1)+D*X2

N. 457:   Y=A*X1**(B+C/LnX2)+D*X2

N. 458:   Y=A*EXP(B*X1+C*X2**2)+D*X2

N. 459:   Y=A*EXP(B*X2+C*X1**2)+D*X2

N. 460:   Y=A*EXP(B/X1+C*X2)+D*X2

N. 461:   Y=A*EXP(B/X2+C*X1)+D*X2

N. 462:   Y=(A+X1)/(B+C*X2)+D*X2

N. 463:   Y=(A+X2)/(B+C*X1)+D*X2

N. 464:   Y=(A+X1)/(B+C*X2**2)+D*X2

N. 465:   Y=(A+X2)/(B+C*X1**2)+D*X2

N. 466:   Y=A*X1**(B*X2**C)+D*X2

N. 467:   Y=A*X2**(B*X1**C)+D*X2

N. 468:   Y=A*X1+B*X2+C*X2**4

N. 469:   Y=A*X1+B/X1**3+C*X2+D/X2**3

N. 470:   Y=A*(X1**B)*Ln(X2+C)+D/X2

N. 471:   Y=A*(X2**B)*Ln(X1+C)+D/X2

N. 472:   Y=A/X1+B*EXP(C/X2)+D/X2

N. 473:   Y=A/X2+B*EXP(C/X1)+D/X2**2

N. 474:   Y=A/X1+B*EXP(C*X2)+D/X2

N. 475:   Y=A/X2+B*EXP(C*X1)+D/X2**2

N. 476:   Y=A*X1**(B+C*X2)+D/X2

N. 477:   Y=A*X2**(B+C*X1)+D/X2

N. 478:   Y=A*X1**(B+C/X2)+D/X2

N. 479:   Y=A*X2**(B+C/X1)+D/X2

N. 480:   Y=A*X1**(B+C*LnX2)+D/X2

N. 481:   Y=A*X2**(B+C*LnX1)+D/X2

N. 482:   Y=A*X2**(B+C/LnX1)+D/X2

N. 483:   Y=A*X1**(B+C/LnX2)+D/X2

N. 484:   Y=A*EXP(B*X1+C*X2**2)+D/X2

N. 485:   Y=A*EXP(B*X2+C*X1**2)+D/X2

N. 486:   Y=A*EXP(B/X1+C*X2)+D/X2

N. 487:   Y=A*EXP(B/X2+C*X1)+D/X2

N. 488:   Y=(A+X1)/(B+C*X2)+D/X2

N. 489:   Y=(A+X2)/(B+C*X1)+D/X2

N. 490:   Y=(A+X1)/(B+C*X2**2)+D/X2

N. 491:   Y=(A+X2)/(B+C*X1**2)+D/X2

N. 492:   Y=A*X1**(B*X2**C)+D/X2

N. 493:   Y=A*X2**(B*X1**C)+D/X2

N. 494:   Y=A*X1+B*X2+C/X2**4

N. 495:   Y=A*X1+B/X1**2+C*X2+D/X2**2

N. 496:   Y=A*(X1**B)*Ln(X2+C)+D/X1

N. 497:   Y=A*(X2**B)*Ln(X1+C)+D/X1

N. 498:   Y=A/X1+B*EXP(C/X2)+D/X1**2

N. 499:   Y=A/X2+B*EXP(C/X1)+D/X1

N. 500:   Y=A/X1+B*EXP(C*X2)+D/X1**2

N. 501:   Y=A/X2+B*EXP(C*X1)+D/X1

N. 502:   Y=A*X1**(B+C*X2)+D/X1

N. 503:   Y=A*X2**(B+C*X1)+D/X1

N. 504:   Y=A*X1**(B+C/X2)+D/X1

N. 505:   Y=A*X2**(B+C/X1)+D/X1

N. 506:   Y=A*X1**(B+C*LnX2)+D/X1

N. 507:   Y=A*X2**(B+C*LnX1)+D/X1

N. 508:   Y=A*X2**(B+C/LnX1)+D/X1

N. 509:   Y=A*X1**(B+C/LnX2)+D/X1

N. 510:   Y=A*EXP(B*X1+C*X2**2)+D/X1

N. 511:   Y=A*EXP(B*X2+C*X1**2)+D/X1

N. 512:   Y=A*EXP(B/X1+C*X2)+D/X1

N. 513:   Y=A*EXP(B/X2+C*X1)+D/X1

N. 514:   Y=(A+X1)/(B+C*X2)+D/X1

N. 515:   Y=(A+X2)/(B+C*X1)+D/X1

N. 516:   Y=(A+X1)/(B+C*X2**2)+D/X1

N. 517:   Y=(A+X2)/(B+C*X1**2)+D/X1

N. 518:   Y=A*X1**(B*X2**C)+D/X1

N. 519:   Y=A*X2**(B*X1**C)+D/X1

N. 520:   Y=A*X1+B*X2+C/X1**4

N. 521:   Y=A*X1+B/X1**3+C*X2+D*Ln(X2)**3

N. 522:   Y=A*(X1**B)*Ln(X2+C)+D*Ln(X2)

N. 523:   Y=A*(X2**B)*Ln(X1+C)+D*Ln(X2)

N. 524:   Y=A/X1+B*EXP(C/X2)+D*Ln(X2)

N. 525:   Y=A/X2+B*EXP(C/X1)+D*Ln(X2)**2

N. 526:   Y=A/X1+B*EXP(C*X2)+D*Ln(X2)

N. 527:   Y=A/X2+B*EXP(C*X1)+D*Ln(X2)**2

N. 528:   Y=A*X1**(B+C*X2)+D*Ln(X2)

N. 529:   Y=A*X2**(B+C*X1)+D*Ln(X2)

N. 530:   Y=A*X1**(B+C/X2)+D*Ln(X2)

N. 531:   Y=A*X2**(B+C/X1)+D*Ln(X2)

N. 532:   Y=A*X1**(B+C*LnX2)+D*Ln(X2)

N. 533:   Y=A*X2**(B+C*LnX1)+D*Ln(X2)

N. 534:   Y=A*X2**(B+C/LnX1)+D*Ln(X2)

N. 535:   Y=A*X1**(B+C/LnX2)+D*Ln(X2)

N. 536:   Y=A*EXP(B*X1+C*X2**2)+D*Ln(X2)

N. 537:   Y=A*EXP(B*X2+C*X1**2)+D*Ln(X2)

N. 538:   Y=A*EXP(B/X1+C*X2)+D*Ln(X2)

N. 539:   Y=A*EXP(B/X2+C*X1)+D*Ln(X2)

N. 540:   Y=(A+X1)/(B+C*X2)+D*Ln(X2)

N. 541:   Y=(A+X2)/(B+C*X1)+D*Ln(X2)

N. 542:   Y=(A+X1)/(B+C*X2**2)+D*Ln(X2)

N. 543:   Y=(A+X2)/(B+C*X1**2)+D*Ln(X2)

N. 544:   Y=A*X1**(B*X2**C)+D*Ln(X2)

N. 545:   Y=A*X2**(B*X1**C)+D*Ln(X2)

N. 546:   Y=A*X1+B*X2+C*Ln(X2)**4

N. 547:   Y=A*X1+B/X1**2+C*X2+D*Ln(X2)**2

N. 548:   Y=A*(X1**B)*Ln(X2+C)+D*Ln(X1)

N. 549:   Y=A*(X2**B)*Ln(X1+C)+D*Ln(X1)

N. 550:   Y=A/X1+B*EXP(C/X2)+D*Ln(X1)**2

N. 551:   Y=A/X2+B*EXP(C/X1)+D*Ln(X1)

N. 552:   Y=A/X1+B*EXP(C*X2)+D*Ln(X1)**2

N. 553:   Y=A/X2+B*EXP(C*X1)+D*Ln(X1)

N. 554:   Y=A*X1**(B+C*X2)+D*Ln(X1)

N. 555:   Y=A*X2**(B+C*X1)+D*Ln(X1)

N. 556:   Y=A*X1**(B+C/X2)+D*Ln(X1)

N. 557:   Y=A*X2**(B+C/X1)+D*Ln(X1)

N. 558:   Y=A*X1**(B+C*LnX2)+D*Ln(X1)

N. 559:   Y=A*X2**(B+C*LnX1)+D*Ln(X1)

N. 560:   Y=A*X2**(B+C/LnX1)+D*Ln(X1)

N. 561:   Y=A*X1**(B+C/LnX2)+D*Ln(X1)

N. 562:   Y=A*EXP(B*X1+C*X2**2)+D*X1

N. 563:   Y=A*EXP(B*X2+C*X1**2)+D*Ln(X1)

N. 564:   Y=A*EXP(B/X1+C*X2)+D*Ln(X1)

N. 565:   Y=A*EXP(B/X2+C*X1)+D*Ln(X1)

N. 566:   Y=(A+X1)/(B+C*X2)+D*Ln(X1)

N. 567:   Y=(A+X2)/(B+C*X1)+D*Ln(X1)

N. 568:   Y=(A+X1)/(B+C*X2**2)+D*Ln(X1)

N. 569:   Y=(A+X2)/(B+C*X1**2)+D*Ln(X1)

N. 570:   Y=A*X1**(B*X2**C)+D*Ln(X1)

N. 571:   Y=A*X2**(B*X1**C)+D*Ln(X1)

N. 572:   Y=A*X1+B*X2+C*Ln(X1)**4

| Back |

Top